The Study of the Tensile Strength of AlSi21CuNiMg Silumin in the Final Stage of Solidification and the Initial Stage of Cooling - Romankiewicz, Remigiusz (Journal of Casting & Materials Engineering, 2019)
The paper presents the results of tensile strength tests of AlSi21CuNiMg silumin made on a test stand. Silumin was under examination in an unmodified state and after modification with AlCu19P1.4 master alloy in quantity of 0.2% in relation to the mass of the alloy. Using a scanning microscope, the surface fractures obtained from tensile tests were tested. The structure and profiles of fractures were examined using an optical microscope. Modification of the tested silumin resulted in a favorable fragmentation and regular distribution of the crystals of the primary silicon in the alloy structure, which led to an almost twofold increase in the strength of the silumin samples at the final solidification stage from 3.5 to 6.6 MPa. As a result of these changes, the resistance of silumin to hot cracks should increase, which is of great importance when casting hypereutectic silumin in a metal mould that strongly inhibits the shrinkage of the castings.